A correlation study on testosterone level with luteinizing hormone to follicle stimulating hormone ratio among women with PCOS in reproductive age - Kumar, Swetha Anil; V. K., Roshna; Prabhakar, Pranav Kumar; C. P., Bineesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
ABSTRACT Background: Polycystic ovarian syndrome (PCOS) is a female specific endocrinological condition. Traits of PCOS include menstrual irregularity, excess hair growth, elevated luteinizing hormone: follicle stimulating hormone (LH-FSH) ratio. The purpose of this study was to investigate any potential correlation between LH-FSH ratio and total testosterone levels in women with PCOS who were of reproductive age. Methods: This cross-sectional study included 50 women with PCOS based on analysis of testosterone, luteinizing hormone, follicle stimulating hormone who have shown PCOS symptoms. The primary emphasis of this investigation was to testing blood samples for hormone levels (LH, FSH, total testosterone). Abott ARCHITECT Ci4100 was used to analyse the blood samples using chemiluminescent microparticle immunoassay (CMIA) chemiflex method. Results: In this study 100 subjects between age 19-45 were taken; 50 were selected as tests and 50 were selected as controls. It has significantly showed a positive correlation with rising testosterone and LH/FSH ratio. Conclusions: Among women with PCOS, the LH-FSH ratio was found to be substantially linked with total testosterone. This aid in a better understanding of the pathophysiology and management of hyperandrogenemia in PCOS women. PCOS cause irregularities of the menstrual cycle, the appearance of clinical manifestations, especially changes of LH/FSH ratio. This ratio can be used to support or confirm PCOS diagnosis along with other tests.